health supervisors’ implementation degree of their tasks and its obstacles from the point of view of the first cycle school principals in Latakia governorate - مسلم, سناء; سلطان , منال; يوسف , سمر (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of this research is to determine the degree to which health supervisors implement their tasks and its obstacles from the point of view of the principals of the first cycle schools in Latakia governorate, And the impact of variables (school location, job, training courses, educational qualification) on that, In order to achieve the objectives of the research, the descriptive approach was used by designing a questionnaire that consisted of (18) phrases distributed on two aspects, As for the research sample, it consisted of (183) male and female principals, and the research reached the following results: The degree of the health supervisors' implementation of their tasks from the point of view of the principals of the first cycle schools in Latakia governorate was medium, while the obstacles to the health supervisors' implementation of their tasks were high. The existence of a statistically significant difference between the average scores of the responses of the research sample members with regard to the degree of health supervisors implementation of their tasks in the first cycle schools in Latakia governorate according to the school location variable (city, countryside). In favor of city schools, there is a statistically significant difference with regard to the obstacles that health supervisors face when carrying out their tasks for the benefit of rural schools. The existence of a statistically significant difference between the average scores of the responses of the research sample members regarding the degree of the health supervisors’ implementation of their tasks in the first cycle schools in Latakia Governorate according to the job variable (full-time health supervisor, administrator in charge of health supervision) in favor of the full-time supervisors and the presence of a statistically significant difference regarding obstacles that faces health supervisors when carrying out their tasks for the benefit of the administrators in charge of health supervision. The existence of a statistically significant difference between the average degrees of the responses of the research sample members regarding the degree of implementation of their tasks by the health supervisors in the first cycle schools in Latakia Governorate according to the variable of training courses in favor of the supervisors who follow more than one course, while there are no statistically significant differences regarding the obstacles to the implementation of the tasks by the health supervisors . There are no statistically significant differences between the mean scores of the responses of the research sample members regarding the degree of health supervisors' implementation of their tasks and their obstacles in the first cycle schools in Latakia Governorate according to the educational qualification variable (intermediate institute, university degree, educational qualification diploma).